Lima Skill Wajib Mahasiswa: Relevan terhadap Karier Masa Depan? - Aulia Adisty Ramdhani; Masduki Asbari; Charlina Nur Assyifa (AGUSPATI RESEARCH INSTITUTA, 2023)
The main purpose of this research is to determine the influence of the skills that college students must have on improving their career in the future. This research used descriptive qualitative method as its method by using a secondary data from one of Sherly Annavita Rahmi's YouTube channel video entitled